2015
DOI: 10.1039/c5py00508f
|View full text |Cite
|
Sign up to set email alerts
|

A squaramide and tertiary amine: an excellent hydrogen-bonding pair organocatalyst for living polymerization

Abstract: A hydrogen-bond motif based on a squaramide and sparteine efficiently promoted the ring-opening polymerization of l-lactide at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Since the first report using 4‐dimethylaminopyridine for the ROP of lactide by Hedrick and coworkers, organocatalysis has drawn great attention in the area of ROP of lactones. Among the organocatalysts based on hydrogen‐bonding motifs, triazabicyclodecene (TBD), recognized as a “magic” catalyst, is one of the most active ones used for the ROP of lactones and has proposed a bifunctional mechanism for the ROPs that activates both the monomer and alcohol initiator through hydrogen bonding . However, the strong basicity and nucleophilicity of TBD lead to the competitive transesterifications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report using 4‐dimethylaminopyridine for the ROP of lactide by Hedrick and coworkers, organocatalysis has drawn great attention in the area of ROP of lactones. Among the organocatalysts based on hydrogen‐bonding motifs, triazabicyclodecene (TBD), recognized as a “magic” catalyst, is one of the most active ones used for the ROP of lactones and has proposed a bifunctional mechanism for the ROPs that activates both the monomer and alcohol initiator through hydrogen bonding . However, the strong basicity and nucleophilicity of TBD lead to the competitive transesterifications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, squaramides may be suitable HB ROP catalysts for lactide polymerization, and their potential in this area remains unexplored. To date, the squaramide‐mediated ROP of lactide was reported on one occasion using a squaramide/(−)‐sparteine two‐component catalytic mixture . While the present study was in progress, a Pt‐functionalized aminosquaramide was also reported to oligomerize lactide …”
Section: Introductionmentioning
confidence: 66%
“…Various H‐bond donor moieties with one, two or three binding sites have been used . b The most common are thioureas, perfluorinated alcohols, phenols, squaramides, sulfonamides, amido–indoles . Combination with organic bases (typically amines or diamines) as H‐bond acceptors afford binary systems.…”
Section: Ring–opening Polymerization Of ε–Caprolactone With (Bis)pyrimentioning
confidence: 99%
“…Various H-bond donor moieties with one, two or three binding sites have been used. 1b The most common are thioureas, 2 perfluorinated alcohols, 3 phenols, 4 squaramides, 5 sulfonamides, 6 amido-indoles.…”
mentioning
confidence: 99%